PENGARUH TEKNIK PEMBELAJARAN SCAFFOLDING TERHADAP KEMAMPUAN MENULIS ARTIKEL ILMIAH POPULER SISWA KELAS XII SMA NEGERI 1 RUNDENG TAHUN PEMBELAJARAN 2024-2025 - Roniati; Teguh Trianton; Yenita Sembiring (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research on the ability to write popular scientific articles aims to explain the influence of learning techniques scaffolding on the ability to write popular scientific articles of Class This research used a Quasi Experimental method involving two groups (two group), namely the experimental class and the control class. The data collection technique uses a test technique in the form of an assignment to write Popular Scientific Articles. Non-test data collection techniques include interviews, observation and obtaining documentation. Hypothesis testing was carried out using the t-test via the IBM SPSS version 25 application. The results of the research showed that learning to write popular scientific article texts using the technique scaffolding that the lowest score in the experimental class was 73 and the highest score was 95 with an average score of 86. The results found that in the experimental class, students were able to write scientific articles well based on the three assessment indicators. The most prominent thing is that students have high scores in the structure adjustment section of popular scientific articles. It is known that the Sig value. (2-tailed) is 0.00 < 0.05. Apart from that, based on the assumptions of the t test, it is obtained that the t count is more basic than the t table with α = 0.05 degrees of freedom (dk/df) = n1 + n2 – 2 = 23 + 22 – 2 = 43. By comparing the t count and t table, 10.231 > 1.681 (t count > t table). On that basis, the hypothesis is accepted is Ha with the hypothesis sounding